Effects of intercropping different quinoa cultivars on peanut rhizosphere microorganisms and yield in saline-alkali soil - Liang, Xiaoyan; Fu, Rao; Chen, Chuanjie; Li, Meng; Yi, Kuihua; Zhang, Haiyang; Gu, Yinyu; Li, Jiajia (Frontiers in Microbiology, 2025)
Intercropping is an effective ecological utilization strategy in saline-alkali land, however, the response of peanut rhizosphere microorganisms in saline-alkali soil to different quinoa cultivars used in intercropping is unclear. In this study, a field experiment was conducted to intercrop peanut (IXP, ILP and IQP) with three quinoa cultivars Xinli 3 (IXQ), Longli 4 (ILQ) and Qinling 2 (IQQ), which differed significantly in plant traits. Illumina-based 16S rRNA gene sequencing was used to investigate the microbial diversity of peanut rhizosphere and to explore the relationship between with environment. The peanuts primarily accumulated sodium (Na) in their roots, especially during the vegetative stage (17.5 g/kg), whereas all plant parts substantially accumulated Na in the reproductive stage. Actinobacteriota and Proteobacteria were the dominant bacterial phyla of peanut rhizosphere, accounting for over 40% of the total bacteria in each group; norank_f__Geminicoccaceae and norank_f__norank_o__Vicinamibacterales were the dominant bacterial genera among all treatments, each exceeding 3.40%. The genus Arthrobacter exhibited the most significant differences in relative abundance among the three quinoa cultivars. The strongest association between peanut rhizosphere microbiota and yield was found when intercropping with IXQ. Stochastic processes dominate the assembly of bacterial communities under intercropping, with IXP exhibiting the highest normalized stochasticity ratio: 68.69% during the vegetative growth stage and 81.11% during the reproductive growth stage. Variance partitioning analysis further showed that peanut rhizosphere bacteria were most strongly correlated with yield (36.1%), followed by nutrient uptake (33.5%) and soil chemical properties (26.6%). Taken together, different quinoa cultivars used for intercropping substantially affected the correlation between peanut rhizosphere microorganisms and soil chemical properties, peanut growth, nutrient uptake, and pod yield, with cultivar IXQ showing the best effects for intercropping with peanuts in saline-alkali soil. These findings provide new insight into the pivotal roles of plant–microbe–yield interactions in abiotic stress mitigation.